Meningkatkan Keterampilan Menulis Paragraf Deskripsi Menggunakan Model Pembelajaran Concept Sentence Di Sekolah Dasar - Nurhaswinda, Nurhaswinda; Kusuma, Yanti Yandri; Hayati, Putri (el-Ibtidaiy:Journal of Primary Education, 2023)
The Students' lack of interest in writing, difficulty expressing ideas, and difficulty distinguishing different paragraph forms are the main causes of the low ability to write descriptive paragraphs. The purpose of this study was to improve students' ability to write descriptive paragraphs in elementary school by using the concept sentence learning model. This research is a classroom action research using two cycles, cycle I and cycle II, with planning, action, observation, and reflection in each cycle. This study tested the writing skills of 24 third grade students of SD Negeri 001 Tanjung. While cycle I and cycle II used test and non-test techniques for data collection, pre-cycle only used test techniques. The assessment used is a test of students' ability to write descriptive paragraphs. The findings of this study lead to the conclusion that the pre-cycle classical mean is 57.52. The average value of the first cycle was 63.92, up 6.4 from the pre-cycle average. The average of the first cycle was 74.64, an increase of 10.72 in the second cycle. In conclusion, the concept sentence learning model can help elementary school students become more proficient in writing descriptive paragraphs.